2006
DOI: 10.1038/sj.emboj.7600940
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic sensory cues generate gustatory plasticity in Caenorhabditis elegans

Abstract: Caenorhabditis elegans shows chemoattraction to 0.1-200 mM NaCl, avoidance of higher NaCl concentrations, and avoidance of otherwise attractive NaCl concentrations after prolonged exposure to NaCl (gustatory plasticity). Previous studies have shown that the ASE and ASH sensory neurons primarily mediate attraction and avoidance of NaCl, respectively. Here we show that balances between at least four sensory cell types, ASE, ASI, ASH, ADF and perhaps ADL, modulate the response to NaCl. Our results suggest that tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
155
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(161 citation statements)
references
References 60 publications
6
155
0
Order By: Relevance
“…One of the conclusions from these results is that multiple CRs expressed in a given cell type converge onto a common set of downstream signal transduction molecules. For example, a number of sensory neuron-specific Gα proteins appear to act in a complex manner to activate or inhibit signaling upon interaction of any ligand with its cognate CR in a given cell type [19,57,[138][139][140]. These G proteins act via different signaling pathways in different chemosensory neuron types.…”
Section: The Molecules For Taste and Smellmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the conclusions from these results is that multiple CRs expressed in a given cell type converge onto a common set of downstream signal transduction molecules. For example, a number of sensory neuron-specific Gα proteins appear to act in a complex manner to activate or inhibit signaling upon interaction of any ligand with its cognate CR in a given cell type [19,57,[138][139][140]. These G proteins act via different signaling pathways in different chemosensory neuron types.…”
Section: The Molecules For Taste and Smellmentioning
confidence: 99%
“…These experiencedependent modulation of adaptation behaviors likely requires integration and processing of information at downstream loci in chemosensory neural circuits [164,165]. However, cell-cell communication between different chemosensory neurons may also play a role in the regulation of responses to a chemical after prolonged exposure [138] (Fig. 3b).…”
Section: Modulation Of Chemosensory Behaviorsmentioning
confidence: 99%
“…Chemotaxis to salt is known to be altered by prior treatment with salt in a paradigm called either gustatory plasticity or salt chemotaxis learning (Saeki et al, 2001;Hukema et al, 2006;Tomioka et al, 2006). Interestingly, treatment of C. elegans in a salt-containing buffer causes a change of chemotaxis from attraction to avoidance of salt.…”
Section: Salt Chemotaxis Learning Causes Reversed Responsesmentioning
confidence: 99%
“…Saeki et al (2001) showed that learned aversion to NaCl generalized to other water-soluble attractants sensed by ASE, including cAMP, biotin, and lysine, suggesting that the changes were occurring at the cellular rather than the receptor level. Using a modified assay in which worms were soaked in a salt buffer without food for just 15 min, Jansen et al (2002) and Hukema et al (2006) identified several components of the molecular pathways acting in at least four sensory neurons to mediate learned NaCl aversion. Relevant molecules include Gg subunit GPC-1, Ga subunits GPA-1 and ODR-3, and TRPV channel subunits OCR-1, OCR-2, and OSM-9.…”
Section: Taste As the Conditioned Stimulusmentioning
confidence: 99%